Pengaruh Model Pembelajaran Kooperatif TGT dan Pembelajaran Berbasis Audiovisual Terhadap Passing Bawah Bolavoli - Akhmad Aji Pradana (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2018)
The purpose of this study was to analyze the effects of TGT cooperative learning and audiovisual media based learning model on volleyball forearm pass skill learning outcome. Method used in this research was quasi experimental design with pretest-posttest approachment. Instrument used in this study were portofolio assessment approach on volleyball forearm pass skill. The result showed that the implementation of TGT cooperative learning model have shown an increased learning output on volleyball forearm pass skill (27.64 %), meanwhile the implementation of learning model using audiovisual media have shown an increased learning output on volleyball forearm pass skill (34.78 %). Based on the result, it was concluded that the implementation of audiovisual media based learning model have shown better improvement on volleyball forearm pass skill learning output.